Improvement of Critical Thinking Ability and Preparedness Assisted by Android-Based Media to Understand Landslide through Physics Learning - Labibah, Ulfaturrona Nur; Mundilarto, Mundilarto; Sulaiman, Syazana bt (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2021)
This research aimed to understand the critical thinking ability improvement and preparedness assisted by Android-based media to understand landslides through physics learning and understand the effectiveness of the media. This research provides knowledge about disaster preparedness through physics learning in landslide-prone schools using Android media. This research used quasi-experimental with Control Group Design. The research subjects included tenth-grade students in class X (30 people) at SMA N 1 Kokap. The samples were selected using the lottery method and saturated sampling technique to determine the control and experiment groups (quasi-experimental with Control Group Design). The pretest and posttest were in the form of essay questions. The analysis data used independent sample T-test and effect size. The results show that the average critical thinking ability of the experimental class increased from 18.13 to 65.00, and the average preparedness increased from 68.75 to 81.88. The results of the independent sample t-test show the value of Sig. (2-tailed) on critical thinking ability was 0.000 and preparedness was 0.027 (Sig. (2-tailed) <0.05). Thus, it can be concluded that there are significant differences in critical thinking ability and disaster preparedness in the experimental class and the control class. The effect size of using an Android-based understanding of landslide natural disasters on students' critical thinking ability and preparedness is 2.0 with high effectiveness. Media landslides and landslides through Android-based physics learning can improve students’ critical thinking ability and disaster preparedness.